2008
DOI: 10.1002/ijc.24044
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and risk of prostate cancer in the health professionals follow‐up study

Abstract: History of diabetes may be associated with decreased prostate cancer (PCa) risk. Published studies have not always accounted for time since diabetes diagnosis or confounding and effect modification by lifestyle factors. The authors investigated the relationship between diabetes and PCa risk in men in the Health Professionals Follow-Up Study from 1986 to 2004. During that time, 4,511 new PCa cases were identified. Multivariate hazard ratios (HR) were estimated using Cox regression. The HR of PCa comparing men w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
135
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(153 citation statements)
references
References 51 publications
13
135
1
4
Order By: Relevance
“…In contrast to the result from the previous studies indicating about the effect of DM on prostate cancer BCR, the present study failed to demonstrate the reduced risk of prostate cancer BCR in diabetic patients. As the duration of DM was not evaluated in the present study, this could be explained by earlier studies which reported that prostate cancer risk is not reduced in the incipient time since DM diagnosis (Rodriguez et al 2005, Kasper et al 2009). Our study has several limitations.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In contrast to the result from the previous studies indicating about the effect of DM on prostate cancer BCR, the present study failed to demonstrate the reduced risk of prostate cancer BCR in diabetic patients. As the duration of DM was not evaluated in the present study, this could be explained by earlier studies which reported that prostate cancer risk is not reduced in the incipient time since DM diagnosis (Rodriguez et al 2005, Kasper et al 2009). Our study has several limitations.…”
Section: Discussionmentioning
confidence: 76%
“…As the 5-year risk of clinical progression in men with BCR ranged from 27 to 60% and BCR typically precedes metastatic progression and prostate cancerspecific mortality by a median of 8 and 13 years, respectively, following radical prostatectomy (Pound et al 1999), it has a clinical significance and is widely used as a critical surrogate marker for disease recurrence. While a number of studies regarding the association between metabolic syndrome and prostate cancer showed inconsistent results (Hå heim et al 2006, Tande et al 2006), type 2 DM was consistently associated with a reduced risk of prostate cancer (Kasper & Giovannucci 2006, Kasper et al 2009, Lawrence et al 2013.…”
mentioning
confidence: 99%
“…This result might be influenced by the significant heterogeneity between the 9 studies included in analysis. Some individual studies though revealed a significant tendency (p trend <0.0001 in the article by Baradaran et al (2009); p trend was 0.01 in the article by Kasper et al (2009); and p trend <0.05 in the article by Zhu et al (2004)). DM is a chronic disease with metabolic syndromes.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 13 relevant studies on the association between DM and PCa have been published since 2006, consisting of 8 prospective studies (Calton et al, 2007;Velicer et al, 2007;Leitzmann et al, 2008;Kasper et al, 2009;Wallstrom et al, 2009;Waters et al, 2009;Li et al, 2010;Lee et al, 2012) and 5 retrospective ones (Gong et al, 2006;Pierce et al, 2008;Baradaran et al, 2009;Pelucchi et al, 2011;Turner et al, 2011). With more than 30,000 additional PCa cases, we aimed to re-analyze this relationship further by conducting an updated detailed meta-analysis with focusing on the effect of time, namely the duration since DM was diagnosed and the age of patient when DM was diagnosed.…”
Section: Diabetes Mellitus Reduces Prostate Cancer Risk -No Function mentioning
confidence: 99%
See 1 more Smart Citation